Database internals a deep dive into how distributed data systems work - Petrov, Alex (O'Reilly Media, 2019)
"When it comes to choosing, using, and maintaining a database, understanding its internals is essential. But with so many distributed databases and tools available today, it's often difficult to learn what each one offers and how they differ. With this practical guide, Alex Petrov guides developers through the concepts behind modern database and storage engine internals. Throughout the book, you'll explore relevant material gleaned from numerous books, papers, blog posts, and the source code of several open source databases. You'll discover that the most significant distinctions among many modern databases reside in subsystems that determine how storage is organized and how data is distributed."--